Hepatoprotective Activity Of Murraya Koenigii Against Ethanolinduced Liver Toxicity Model In Experimental Animals - SADHANA SATHAYE,; POORNIMA D AMIN,; VINAM B MEHTA,; VIJAY B ZALA,; RAMESH D KULKARNI,; HARPREET KAUR,; ROOPALI G REDKAR, (International Journal of Pharma and Bio Sciences, 2012)
Murraya koenigii (Linn) Spreng (Indian curry leaf) is a highly valued culinary plant with the aqueous extract of its leaves which are reported to exhibit diverse biological activities. Considering free radical mechanism in hepatotoxicity, dietary antioxidants could provide protection in conditions including alcoholic liver disease. The objective of this study was to investigate its effects on biochemical markers of liver function affected in diseased state. Two high doses of 1 g/kg and 2 g/kg were evaluated for its hepatoprotection on ethanol-induced liver toxicity in Wistar rats. The aqueous extract showed potent antioxidant activity, and at both doses produced a significant increase in reduced glutathione levels with comparable reduction in serum glutamate pyruvate transaminase and alkaline phosphatase levels. Only 1 g/kg dose depleted malondialdehyde levels in comparison to ethanol. Histopathology of liver samples confirmed the above findings. The results suggested significant benefits of nutritive antioxidant compounds in M. koenigii contribute to its potential hepatoprotective activity